Hydrogen production from biodiesel industry waste by using a co-culture of Enterobacter aerogenes and Clostridium butyricum. Issue 6 (2nd November 2017) - Pachapur, Vinayak Laxman; Sarma, Saurabh Jyoti; Brar, Satinder Kaur; Bihan, Yann Le; Buelna, Gerardo; Verma, Mausam
ABSTRACT: Valorization of crude glycerol (CG), a waste of biodiesel production process, was investigated for increased hydrogen production by co-culture system using Enterobacter aerogenes NRRL B-407 and Clostridium butyricum NRRL B-41122. The ability of E. aerogenes was evaluated as a replacement of expensive reducing agent to maintain anaerobic conditions for the growth of C. butyricum . The co-culture resulted in increased hydrogen production, reaching a maximum of 19.46 ± 0.95 mmol-H2 /L-medium in comparison to monoculture of E. aerogenes (15.64 ± 0.47) and C. butyricum (17.44 ± 0.38) in the presence of reducing agent. The effect of inoculum ratio was investigated and hydrogen yield was 0.95 mmol-H2 /mol-glycerol at 1:11 inoculum ratio with more than 85% of substrate utilization was comparable to other mixed and co-culture studies. In addition to hydrogen, value added by-products such as 1, 3-propandiol, acetic acid, butyric acid and ethanol have also been produced. Co-culture indicated the possibility of valorization of CG as a stable functional consortium with higher conversion efficiency for increased hydrogen along with high value by-product production. Additionally, the study provided the evidence of medium composition controlled metabolic pathway shift during CG bioconversion. Valorization of low cost CG with efficient co-culture of hydrogen production can aid biodiesel in-house energy source.